TRANSFORMASI BISNIS DI ERA DIGITAL: PERAN TEKNOLOGI INTERNET DALAM MENGEMBANGKAN E-BISNIS - Laksamana Khaidir K.N., Laksamana Khaidir K.N.; Nuragustin; Sri Adel Febri Aldina; Nurul Noviyana; Nurbaiti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
Digital business transformation is crucial for companies in the digital era, especially through the role of internet technology in fostering e-business growth. This study aims to identify the role of internet technology in e-business and the challenges of digital transformation. Using a descriptive qualitative method through literature review, this study finds that the implementation of technologies like IoT, AI, and cloud computing enhances operational efficiency, expands market reach, and improves customer experience. However, companies face obstacles, including resistance to change and high technology investment costs. With the right strategies, digital transformation enables companies to compete and adapt in the dynamic digital market. Keywords : Digital Transformation, Internet Technology, E-Business, IoT, AI, Cloud Computing